Love your enemy? An aesthetic discourse analysis of self-transcendence in values-motivated altruism. Issue 4 (2nd October 2018) - Mitchell,; Eiroa-Orosa,
Abstract : ABSTRACT Inter-disciplinary academic enquiry shares the challenge to explore the social and ethical applications of research into today's globalised but increasingly complex world. Positive psychology examines how life can be well in this broader enquiry of the social and moral contexts of 'individual' happiness. In this it begins to embrace innovative, qualitative research methods alongside its earlier positivistic, scientific approach, in the social transition to enquire more inductively. This research therefore attempts two things. The substantive research explores how experiences of self-transcendence may emerge in the choice of altruistic values, to 'love an enemy', potentially at cost to personal 'selfhood' in pursuit of a well society. Secondly, it presents the innovative 'aesthetic discourse analysis' as a means to examine the motivational or moral impulse of personhood, where the self becomes 'sensible' to agentic change. It draws on Bakhtin's use of genre, emotional intonation and chronotope to interrogate the 'feltness' of self-conscious motivation. In three focus groups, people who are all committed to the self-transcendent value to love the Other, converse with Others from different backgrounds and belief systems. The research discovers that lived experiences of self-transcendence co-occur with ontological and epistemological re-shaping of self-consciousness.